Hyphal Branching during Arbuscule Development Requires Reduced Arbuscular Mycorrhiza1. Issue 4 (28th October 2015) - Park, Hee-Jin; Floss, Daniela S.; Levesque-Tremblay, Veronique; Bravo, Armando; Harrison, Maria J.
Abstract : A plant transcription factor regulates the expression of genes necessary to enable arbuscular mycorrhizal fungi to develop branched hyphae in root cortical cells. Abstract: During arbuscular mycorrhizal symbiosis, arbuscule development in the root cortical cell and simultaneous deposition of the plant periarbuscular membrane generate the interface for symbiotic nutrient exchange. The transcriptional changes that accompany arbuscule development are extensive and well documented. By contrast, the transcriptional regulators that control these programs are largely unknown. Here, we provide a detailed characterization of an insertion allele of Medicago truncatula Reduced Arbuscular Mycorrhiza1 (RAM1), ram1-3, which reveals that RAM1 is not necessary to enable hyphopodium formation or hyphal entry into the root but is essential to support arbuscule branching. In ram1-3, arbuscules consist only of the arbuscule trunk and in some cases, a few initial thick hyphal branches. ram1-3 is also insensitive to phosphate-mediated regulation of the symbiosis. Transcript analysis of ram1-3 and ectopic expression of RAM1 indicate that RAM1 regulates expression of EXO70I and Stunted Arbuscule, two genes whose loss of function impacts arbuscule branching. Furthermore, RAM1 regulates expression of a transcription factor Required for Arbuscule Development ( RAD1 ). RAD1 is also required for arbuscular mycorrhizal symbiosis, and rad1 mutants show reduced colonization. RAM1 itself is induced in colonized root cortical cells, and expression of RAM1 and RAD1 is modulated by DELLAs. Thus, the data suggest that DELLAs regulate arbuscule development through modulation of RAM1 and RAD1 and that the precise transcriptional control essential to place proteins in the periarbuscular membrane is controlled, at least in part, by RAM1.